2015
DOI: 10.5858/arpa.2015-0240-sa
|View full text |Cite
|
Sign up to set email alerts
|

New Markers for Separating Benign From Malignant Mesothelial Proliferations: Are We There Yet?

Abstract: The separation of benign from malignant mesothelial proliferations is crucial to patient care but is frequently morphologically difficult.Context.— To briefly review adjunctive tests claimed to be useful in this setting and to examine in detail 2 new tests: p16 fluorescence in situ hybridization (FISH) and BRCA1-associated protein 1 (BAP1) immunohistochemistry.Objective.— Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
154
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 42 publications
4
154
0
2
Order By: Relevance
“…However, not all mesotheliomas harbor this deletion, and the sensitivity for epithelioid/biphasic MPM ranges from approximately 45% to 85%. The sensitivity of the p16 FISH test is much higher in sarcomatoid mesothelioma; in some reports, the deletion is reported in up to 100% of cases; however, other studies report a lower proportion of p16-deleted sarcomatous tumors (16).…”
Section: Reactive Mh Versus Epithelioid/mixed Mpmmentioning
confidence: 96%
See 4 more Smart Citations
“…However, not all mesotheliomas harbor this deletion, and the sensitivity for epithelioid/biphasic MPM ranges from approximately 45% to 85%. The sensitivity of the p16 FISH test is much higher in sarcomatoid mesothelioma; in some reports, the deletion is reported in up to 100% of cases; however, other studies report a lower proportion of p16-deleted sarcomatous tumors (16).…”
Section: Reactive Mh Versus Epithelioid/mixed Mpmmentioning
confidence: 96%
“…Several recent studies have shown that the homozygous deletion of p16 by FISH is found only in mesotheliomas, whereas none of benign mesothelial proliferations showed a loss of p16 with a specificity of 100% (16,(25)(26)(27). However, not all mesotheliomas harbor this deletion, and the sensitivity for epithelioid/biphasic MPM ranges from approximately 45% to 85%.…”
Section: Reactive Mh Versus Epithelioid/mixed Mpmmentioning
confidence: 98%
See 3 more Smart Citations